Radiation-Induced Paramagnetic Centers in Meso- and Macroporous Synthetic Opals from EPR and ENDOR Data - Alexander Rodionov; Larisa Latypova; Georgy Mamin; Marat Gafurov (Magnetochemistry)
The paramagnetic defects and radiation-induced paramagnetic centers (PCs) in silica opals can play a crucial role in determining the magnetic and electronic behavior of materials and serve as local probes of their electronic structure. Systematic investigations of paramagnetic defects are essential for advancing both theoretical and practical aspects of material science. A series of silica opal samples with different geometrical parameters were synthesized and radiation-induced PCs were investigated by means of the conventional and pulsed X- and W-band electron paramagnetic resonance, and 1H/2H Mims electron-nuclear double resonance. Two groups of PCs were distinguished based on their spectroscopic parameters, electron relaxation characteristics, temperature and time stability, localization relative to the surface of silica spheres, and their origin. The obtained data demonstrate that stable radiation-induced E’ PCs can be used as sensitive probes for the hydrogen-containing fillers of the opal pores, for the development of compact radiation monitoring equipment, and for quantum technologies.